Strategic Management Analysis For Sustainable Business Performance PT X - Noviandar, Rully; Sihite, Mombang; Derriawan, Derriawan (Green Publisher, 2025)
In a business era full of uncertainty and high competitive dynamics, the company's ability to develop and execute mature strategic management is the main determinant in maintaining business sustainability. The purpose of this study is to analyze and evaluate the application of strategic management at PT X through a comprehensive approach, starting from the analysis of mission statement components, SWOT analysis, IFE and EFE Matrix, Competitive Profile Matrix (CPM), to Strategic Position and Action Evaluation (SPACE) Matrix, as well as the design of corporate strategy using The Three Horizons model. This study uses a descriptive qualitative method with a case study approach. The data collection technique includes a study of documents on the financial and annual statements of PT X and its subsidiaries from 2012–2019, then financial and annual report data of three companies for benchmarking. The results showed that PT X had significant internal strength (IFE score 3.04) but was less than optimal in responding to external dynamics (EFE score 2.61). The proposed corporate strategy includes strengthening core business (H1), transforming business unit portfolio (H2), and long-term innovative development (H3). This research is expected to be an initial reference for follow-up studies that can enrich the analysis of business strategies through additional approaches such as PESTLE and Balanced Scorecard to establish more holistic sustainable performance indicators.